Design of D022 superlattice with superior strengthening effect in high entropy alloys. (1st April 2019) - He, Feng; Chen, Da; Han, Bin; Wu, Qingfeng; Wang, Zhijun; Wei, Shaolou; Wei, Daixiu; Wang, Jincheng; Liu, C.T.; Kai, Ji-jung
Abstract: Precipitation strengthening is one of the most promising mechanisms to develop high-performance high entropy alloys (HEAs). However, the design of a reinforcing phase with an excellent strengthening effect is still one of the most pivotal challenges. In the present study, a design strategy based on overall valence electron concentration (OVEC) is developed, and a coherent D022 superlattice (noted as γ″ phase) with superior strengthening effect is designed. The newly developed γ″ phase is systematically characterized using transmission electron microscope and atom probe tomography. Differentiating from the traditional Ni3 Nb γ″ phase, the present high-entropy γ″ phase contains ∼7.7% Co and follows the (Ni, Co, Cr, Fe)3 (Nb, Fe) stoichiometry. Three γ″ phase variants are observed with crystallographic orientation relationships of [001]γ″ //<001>γ and (001)γ″ //{100}γ . The lenticular γ″ particles with small volume fraction (7%) causes a significant yield strength increase (670 MPa) and ductility retention (40%), resulting in excellent yield strength-ductility combination. The excellent strengthening effect of the γ″ phase is attributed to both ordering strengthening and coherency strengthening. The present study proposes a new design strategy of precipitates and develops a superior reinforcing phase for HEAs. These findings will not only promote the development of precipitation-hardened HEAs but deepen the fundamentals of precipitates design for other complex concentrated alloys as well. Graphical abstract: Image 1